PELAKSANAAN PROGRAM PENGEMBANGAN PEMASARAN PARIWISATA DALAM MENDUKUNG OBJEK WISATA BONO DI KABUPATEN PELALAWAN TAHUN 2019 - Indah Niwanda; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Bono Tourism Object is a natural phenomenon that occurs in the Kampar River, Teluk Meranti, Pelalawan Regency. The development of tourism sites makes the government need to strengthen the tourism program, especially Bono natural tourism which is well known throughout the world. The implementation of the Tourism Marketing Development Program is one of the programs created by the government to introduce Bono to the annual Bekudo Bono Festival Activities, namely a culture-based surfing sport event by combining traditional surfing sports carried out on river waves which are quite unique. The purpose of this study is to determine the implementation of the marketing development program at the Bono tourist attraction in 2019 and want to know the inhibiting factors in the implementation of this program. This research uses a qualitative approach with descriptive methods. In data collection, the authors use interview techniques, mass media, and documentation . The results of this study found that there are three elements called the suitability model, namely the program, program implementer, and program objectives. In the first element, the alignment of the Marketing Development program at Bono Tourism Objects with the program target needs is good, where this program is designed and adapted to In the second element, program implementers in this case are not optimal, there are still program implementers who do not understand the duties and functions of their fields. In the third element, namely the program target, there are still people who have not felt the benefits of this program. The presence of influencing factors in this program, both external and internal, has made the implementation of the Marketing Development Program in Support of Bono Tourism Objects not fully realized. Keywords: Program Implementation, Bono Tourism Object Marketing, Program, Program Implementation, Program Objectives.